There is no Planet B a handbook for the make or break years - Mike Berners-Lee (New York Cambridge University Press, 2020)
Feeding the world, climate change, biodiversity, antibiotics, plastics, pandemics - the list of concerns seems endless. But what is most pressing, and what should we do first? Do we all need to become vegetarian? How can we fly in a low-carbon world? How can we take control of technology? And, given the global nature of the challenges we now face, what on Earth can any of us do, as individuals? Mike Berners-Lee has crunched the numbers and plotted a course of action that is full of hope, practical, and enjoyable. This is the big-picture perspective on the environmental and economic challenges of our day, laid out in one place, and traced through to the underlying roots - questions of how we live and think. This updated edition has new material on protests, pandemics, wildfires, investments, carbon targets and of course, on the key question: given all this, what can I do?
Includes bibliographical references and index.
Keywords: Power resources